Cognitive Dissonance dalam Perilaku Diet: Kajian Literatur Teoritis dan Empiris - Syalsa Maulina Sitompul; Neviyarni S (PT. Hasba Edukasi Mandiri, 2025)
Cognitive Dissonance Theory, developed by Leon Festinger (1957), explains that inconsistency among an individual’s beliefs, attitudes, and actions generates psychological tension known as dissonance. This article analyzes the phenomenon of cognitive dissonance in the context of eating behavior and dieting through a literature review of classical theories and recent empirical findings. The review indicates that individuals experiencing dissonance during the dieting process tend to employ various reduction mechanisms, such as internal justification, minimizing the importance of inconsistency, and gradual behavioral change. The effectiveness of dissonance management is influenced by environmental and social factors, including exposure to food advertising, social pressure, cultural identity, and support from the immediate social environment. This review highlights the relevance of cognitive dissonance theory in understanding the dynamics of dieting behavior and as a conceptual foundation for the development of health interventions grounded in social psychology. This article adopts a narrative literature review approach by examining theoretical and empirical literature published between 2015 and 2024.